Enhancing professionalism in post-graduate medical education: the initial implementation and evaluation of a longitudinal curriculum for geriatrics residents in Toronto, Canada - Kokorelias, Kristina M; Sheikh, Muhammad Harris; Naimi, Maryam; Ho, Bernice; Wong, Edwin W; Brooks, Stephanie G; Gandell, Dov; Berger, Arielle S (Canadian Medical Education Journal, 2025)
Background: Professionalism is vital in medicine, yet gaps exist in its teaching within post-graduate medical education (PGME). Methods: We developed an eight-session curriculum on professionalism for geriatrics residents at the University of Toronto. Topics included personal-professional identity, physician well-being, communication, and leadership, incorporating a focus on self-reflection throughout. We evaluated the curriculum in two ways: (1) we captured immediate reactions using standard evaluations with Likert-scale questions on teaching effectiveness. (2) Graduated residents participated in semi-structured interviews to assess deeper reactions and longer-term impacts on professional identity and practice. Interview transcripts were rigorously analyzed using thematic. Results: The teaching effectiveness scores averaged from 80 written evaluations were excellent: 4.45/5 (89%). We interviewed 12 of 22 eligible graduates (55%). Thematic analysis demonstrated that the curriculum impacted residents in three key thematic areas: (1) it led participants to understand their role as physicians in a more comprehensive way, while staying consistent with their personal values and strengths. (2) Communication skills training in particular equipped learners with important skills needed to enact their professional standards. (3) Through developing a supportive community and practicing mindful self-reflection, participants reported improvements in their well-being. Conclusions: This paper demonstrates that professionalism can and should be integrated into the formal curriculum of post-graduate medical education. Key success factors in our study included a focus on fostering peer support and training in communication skills as a concrete method to actualize personal professional standards.